Attention set for number: expectation and perceptual load in inattentional blindness. - White, R; Aimola Davies, A (2008)
Inattentional blindness is the failure to detect unexpected events when attention is otherwise engaged. Previous research indicates that inattentional blindness increases as perceptual demands intensify. The authors present 6 cuing experiments that manipulated both the perceptual demands of a primary letter-naming task and the expectations of the individual. Inattentional blindness was greatest for individuals who held a numerical expectation that was consistent with the number of primary-task items presented. Expectation also affected detection differentially at various levels of perceptual load: Detection at moderate and high perceptual load was significantly affected by expectation, whereas detection at low perceptual load was not. The authors suggest that at moderate to high levels of perceptual load, individuals whose numerical expectations are fulfilled terminate processing when the primary task is complete, at the expense of the unexpected visual event. These experiments provide compelling evidence that expectations do affect detection of an unexpected stimulus, and they are the first to demonstrate that individuals set their attention for the number of items to be detected and are vulnerable to inattentional blindness whenever their primary-task numerical expectation is fulfilled.